Consistency of Planning, Budgeting, and Achievement of Pro-Poor Budget Targets in Jembrana Regency - Syofia Sofatunisa Ramdayani (Universitas Bangka Belitung, 2024)
Pro-Poor Budgeting is one of the steps of intensive government that is carried out in order to countermeasure poverty. To achieve the pro-poor budgeting target, consistency between document planning and budgeting is necessary. However, facts on the ground show that guarding consistency is not an easy thing​ so inconsistency is often found and still becomes an inhibitor in the achievement vision and mission development area. Research This aims to know how far the consistency and achievement between document budget RPJMD, RKPD, RENSTRA, and RENJA is in the Regency Jembrana 2021. Methods used in the study are descriptive qualitative and quantitative. Research results prove that in a way overall level of consistency between fifth related fields​ with pro-poor budgeting being in the category of Good However level of consistency is highest achieved by the field of education. While that, level average program and budget achievements have been enough good. Condition the prove that still there is inconsistency a number of indicators of programs and activities that have been arranged in document planning. Therefore the government needs to make an effort to frame lower poverty continously.